The Effect Of Using Chicken Egg Emulsifier And Duck Eggs On The Quality Of Ice Cream - Octaliandra, Selly; Holinesti, Rahmi (Universitas Negeri Padang, 2022)
Ice cream is a product derived from dairy processing and has a semi-solid texture and is consumed frozen. One of the most important ingredients in the manufacture of ice cream is emulsifier. Emulsifier consist of two types, namely natural emulsifiers and artificial (synthetic) emulsifiers. Artificial or synthetic emulsifiers come from human engineering, namely engineered fats while natural emulsifiers usually come from nature such as egg yolks. The use of egg yolks with the right concentration can increase the viscosity, texture and consumer liking. This study aims to analyze the quality of ice cream using an emulsifier from chicken eggs and duck eggs on the quality of color, aroma, texture, and taste of ice cream. This type of research is a pure experiment with a completely randomized design method (CRD) by studying two treatments X1 (duck egg yolk), X2 (chicken egg yolk) with 3 repetitions. The data collection technique was carried out by conducting an organoleptic test involving five expert panelists who were Lecturers of Catering Department of Family Welfare, Faculty of Tourism, Hospitality, Padang State University. The results obtained from the organoleptic test will be continued with statistical analysis using the T test. The results show that there are significant differences in the quality of color, aroma and taste in ice cream and there is no effect on the quality of texture. The best results were found in the X1 treatment, namely the use of duck eggs on the quality of ice cream